2022
DOI: 10.3390/nu14050956
|View full text |Cite
|
Sign up to set email alerts
|

The Serial Mediation of the Association between Breakfast Skipping and Suicidality by Weight Status and Depressive Symptoms: Findings from the National Youth Risk Behavior Surveys of the United States

Abstract: Background: The evidence is limited for the dose–response association between breakfast skipping and suicidality. The underlying pathway from breakfast skipping to suicidality has also rarely been explored in previous studies. Methods: The data of Youth Risk Behavior Surveys (YRBSs) of the United States from 2011 to 2019 were used with a sample size of 74,074. The male: female ratio was nearly 1:1. Binary logistic regression models with complex sampling design were adopted to show the effect of breakfast skipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Previous study has shown that depression and weight gain are mediated to affect suicide risk such as suicidal ideation and suicide plan. 15 However, in our study, not only emotional factors but also non-emotional factors such as grades and socioeconomic status were considered. In particular, we have confirmed that there was a significant difference in suicide attempts according to socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study has shown that depression and weight gain are mediated to affect suicide risk such as suicidal ideation and suicide plan. 15 However, in our study, not only emotional factors but also non-emotional factors such as grades and socioeconomic status were considered. In particular, we have confirmed that there was a significant difference in suicide attempts according to socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Skipping breakfast in adolescents is known to increase the risk of suicidal thoughts and suicide plans. 15 , 16 It is possible that these processes were mediated by depressive symptoms. 15 A meta-analysis of the relationship between breakfast and depression found that skipping breakfast was associated with a higher risk of depression and anxiety (OR = 1.39; 95% CI = 1.34–1.44, OR = 1.51; 95% CI = 1.25–1.77); however, it had nothing to do with stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it was shown that only in the first group was there a deterioration of the psychoemotional state [28], indicating that eating at night is a risk factor for depression. Breakfast skipping is associated with depression [29] and decreased academic performance [30] in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…A further meta-analysis including 399,550 individuals found a significant association between skipping breakfast and depression (pooled odd ratio (OR): 1.39, 95% CI: 1.34-1.44), stress (pooled OR: 1.23, 95% CI: 1.04-1.43), and psychological distress (pooled OR: 1.55, 95% CI: 1.47-1.62) [4]. In this Special Issue, Liu et al highlighted the increased risk of suicide in adolescents enrolled in the Youth Risk Behavior Surveys (YRBSs), where being overweight/obese seems mediate the association between skipping breakfast and suicidality [5].…”
mentioning
confidence: 99%